Real-time transmission of time-lapse imagery of glaciers in the southern Andes - Carvallo Barrientos, Ruben Alfonso; Llanos, Pablo; Noceti, Rodrigo; Casassa, Gino (My University, 2017)
Time-lapse cameras provide valuable imagery for the study of the environment and ecosystems. In the case of glaciers, they can be used to monitor Glacial Lake Outburst Floods (GLOFs), ice calving of tidewater and freshwater fronts, ice velocity, glacier albedo and geometric changes. Custom-made time-lapse cameras from off-the-shelf components have been installed at glacier fronts in Fuego-Patagonia and central Chile for monitoring of albedo, velocity and ice calving. Time-lapse images are generally of high resolution and constitute large data sets which are normally used in post-processing mode, retrieving the imagery in the field every few months or even at a yearly time interval. Real-time availability of the imagery is of high interest in special cases such as early-warning systems, monitoring of large changes which require urgent field measurements, and also for detection of lapse-rate camera failure. We present here a low-cost data transmission system which allows to transmit in real-time full resolution images in a few seconds via 2 GHz and 5 GHz Wi-Fi, with a bandwidth of 80 Mbps. The camera is controlled by a Raspberry Pi single-board computer which is also used to store and transmit the photographs. Technical characteristics are presented, including successful laboratory experiments and future field deployment issues.
Keywords: digital photograph; glacier; raspberry; time-lapse camera; transmission; wi-fi